THE EFFECT OF FOOD QUALITY ON GUEST SATISFACTION OF IBIS ARCADIA JAKARTA HOTEL - Indriani, Putri; Nugraha, Rizki Nurul; Ardani, Putri Aulia (Jurnal Manajemen Pelayanan Hotel, 2022)
This study was conducted to determine the effect of food quality on consumer satisfaction at the Ibis Arcadia Hotel. This study used quantitative methods with a total of 44 respondents. This analysis technique uses a simple regression technique and has Variable X for Food Quality and Variable Y for Consumer Satisfaction. The data collection method in this study used a questionnaire that was measured on a Likert scale. The instrument tests in this study are validity tests, reliability tests, and classical assumption tests (normality tests and linearity tests). For data analysis techniques using simple regression analysis. Test the hypothesis using the t-test. The results showed that food quality has a significant influence on the satisfaction of Ibis Arcadia Jakarta hotel guests. Keywords: Food quality, Customer Satisfaction, Hotel